Analisis Strategi Pemasaran Yang Terjadi Pada Usaha UMKM di Kota Medan Saat Masa Pandemi Covid-19 - Ridho Fachrozie; Nuri Aslami (Universitas Muhammadiyah Enrekang, 2022)
The number of MSMEs in Indonesia reached 65.47 million units in 2019. This number increased by 1.98% compared to 64.19 million units in the previous year. This amount reaches 99.99% of the total business in Indonesia. The pandemic that occurred in Indonesia caused many people to lose their jobs, and shift their jobs to the MSME sector, and certainly had an impact on competition between MSME traders, which then many MSME traders implemented special strategies to stay competitive. The purpose of this research is that we know what marketing strategies are used by MSME traders during the COVID-19 pandemic in the city of Medan. The approach taken in this research is to use a qualitative approach by using the literature study method. The data of this research was obtained by collecting writings from several articles, several books and all forms of sources related to the object of research. The results of this study indicate the marketing strategy of MSMEs in the city of Medan